(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the educational, moral, and spiritual importance of kurash sports in the upbringing of student youth, highlighting it as a means of moral-ethical education. Information is provided about how kurash, both in the educational process and in sports competitions, serves as a source of national pride and honor, and plays a significant role in the comprehensive development of the individual.